(untitled) (Tamaddun, 2025)
Academic writing is a formidable challenge for English as a Foreign Language (EFL) learners, with motivation being a critical determinant of success. This systematic literature review synthesizes the theoretical and empirical landscape of motivation in EFL academic writing. It traces the evolution of key conceptual frameworks, from foundational dichotomies to contemporary socio-dynamic models like the L2 Motivational Self System. A thematic analysis of the literature identifies three core clusters of motivational determinants: the writer’s internal world (e.g., self-efficacy, attributions), the nature of the writing task (e.g., choice, authenticity), and the learning environment (e.g., teacher support, classroom climate). The review further examines the motivational impact of pedagogical interventions, including various forms of feedback and the integration of technology from collaborative platforms to generative AI. The discussion proposes an integrated model where motivation emerges from the interplay of identity, agency, and context, highlighting critical research gaps and outlining a forward-looking agenda.